Ammonia-controlled synthesis of monodispersed N-doped carbon nanoparticles. (1st September 2020) - Hanif, Farzana; Liu, Yingcen; Liu, Jihong; Song, Caicheng; Zhang, Liyan; Lin, Hua; Lu, Rongwen; Zhang, Shufen
Abstract : The presence of ammonia slowing down the acid-catalysed Schiff base formation as well as control the monodispersity through the separation of nucleation and growth stages. Abstract : Synthesis of monodispersed nanoparticles has been a research frontier in the field of materials chemistry. However, developing a method for controlled synthesis of monodispersed nanoparticles has always been a challenge. Herein, we demonstrate an effective controlled synthesis strategy through simple selection of the reactant used for the polymeric precursor formation of N-doped carbon nanospheres (N-CNs). Specifically, ammonia was introduced into a reaction system that consisted of para -phenylenediamine ( p -PDA) and formaldehyde (HCHO), and a reaction between ammonia and HCHO occurred preferentially, resulting in controlled release of HCHO, and continuous supply for the reaction of p -PDA and HCHO at the growth stage, separate from the nucleation event. In this way, controllable formation of monodispersed polymer nanospheres could be achieved, and the size of the nanospheres could be tuned by changing the molar ratio of ammonia to HCHO. The action of ammonia to control HCHO for the synthesis of monodispersed nanospheres has been investigated by UV-visible spectrophotometry and NMR spectroscopy.